2009
DOI: 10.1093/sleep/32.11.1417
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation Specifically Impairs Short-term Olfactory Memory in Drosophila

Abstract: We found that slpD specifically impaired 1-h memory in Drosophila, and either silencing of MB transmission during slpD or down-regulation of the cAMP level in the MB protected the flies from slpD-induced impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 45 publications
5
61
1
2
Order By: Relevance
“…The lack of a homeostatic response seen in for R flies may represent either an adaptation that allows animals to better withstand the negative effects of waking, or it may indicate that foraging disrupts regulatory processes, thereby preventing flies from obtaining needed sleep. Because deficits in short-term memory are a robust consequence of sleep loss (13,22,23), we evaluated short-term memory (STM) using aversive phototaxic suppression (APS) in for R , for s , and for s2 flies following 12 h of SD. In the APS, flies are individually placed in a T maze and allowed to choose between a lighted and darkened chamber (13,24).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of a homeostatic response seen in for R flies may represent either an adaptation that allows animals to better withstand the negative effects of waking, or it may indicate that foraging disrupts regulatory processes, thereby preventing flies from obtaining needed sleep. Because deficits in short-term memory are a robust consequence of sleep loss (13,22,23), we evaluated short-term memory (STM) using aversive phototaxic suppression (APS) in for R , for s , and for s2 flies following 12 h of SD. In the APS, flies are individually placed in a T maze and allowed to choose between a lighted and darkened chamber (13,24).…”
Section: Resultsmentioning
confidence: 99%
“…However, despite a long standing interest in the circadian regulation of Drosophila 50 activity, little was known about the biological characteristics of the mainly nocturnal resting state until the year 2000, when two independent laboratories demonstrated that the prolonged inactivity observed in Drosophila fully satisfies the five behavioural characteristics that define a sleep-like status 2 : (i) consolidated circadian periods of immobility, (ii) a species-specific posture and/or resting place, (iii) an increased arousal threshold, (iv) reversibility to wakefulness and (v) a 55 homeostatic regulatory mechanism 3,4 . We now know that sleep loss has similar detrimental effects on flies as it has on mammals 5,6 and that social experience modulates sleep need in Drosophila, as it does in vertebrates 7,8 . Conservation of sleep from humans to flies extends beyond behaviour to pharmacology (e.g.…”
Section: Overviewmentioning
confidence: 99%
“…Flies, like vertebrates, show both cognitive and physical impairments upon prolonged sleep deprivation with consequences that range from learning deficits to death 6,18 . There are several ways to perform sleep deprivation in Drosophila: pharmacological; mechanical; social; and starvation-induced.…”
Section: Choice Of Computermentioning
confidence: 99%
See 1 more Smart Citation
“…Acute sleep deprivation and chronic sleep restriction cause significant decrements in short-term and long-term memories in humans and in animal models. [3][4][5][6][7][8][9] In mammals, the consolidation of hippocampal dependent spatial memory is particularly susceptible to the effects of sleep deprivation. [10][11][12] In Drosophila and mouse models, genetic mutants exhibiting reduced sleep also show impairments in memory.…”
Section: Introductionmentioning
confidence: 99%